اردو اسلامی ادب میں رفیع الدین ہاشمی کی خدمات کا مطالعہA Study of the Services of Rafī-ud-Dīn Haāshmī in Urdu Islamic Literature (Al-Qamar, 2020)
This article studies the contribution of Rafī-ud-Dīn Haāshmī (Born 1940), a renowned Pakistani scholar of Urdu language and literature. His literary contributions towards various branches of Urdu literature have been appreciated among the literary circle. His attachment with the manifesto of Islamic movement is reflected in his writings. He condemned the non-Islamic traditions, style and ways of living in his writings. He pointed out the weaknesses of socialism in comparison with that of Islam. Hāshmī clearly mentioned the anti-masses manifesto of socialist form of government in his articles like “Socialism and Religion”, “Socialism and Democracy”, “Social and Farmers” and “Socialism and Suppression”. He presented a complete programmer for spiritual training of individual and society as well as social stability in his article named: “Shab Bedārī”. His other notable contributions discussed here are “Khutbāt-i-Rasūl”, “Seerat-i-Sarwar-e-ʻĀlam” and “Iqbal aur Mīir-i-Hijāz”. His writings and articles had a profound effect on the readers.
Keywords: Rafī-ud-Dīn Haāshmī’s; contribution; Urdu Islamic Literature